Characterisation of ciguatoxins. Issue 5 (19th May 2021) - Gago‐Martinez, A.; Leão, J.M.; Estevez, P.; Castro, D.; Barrios, C.; Hess, P.; Sibat, M.
Abstract : The primary objective of this specific grant was to characterize the risk associated to Ciguatera Poisoning (CP) in the EU by developing a sensitive methodology of LC‐MS/MS. The preparation of reference materials including the main ciguatoxins (CTXs) responsible for the contamination was considered the secondary objective to facilitate the implementation of the LC‐MS/MS methods in the EU laboratories to characterize this emerging risk. C‐CTX1 has been identified by LC‐MS/MS, and further confirmed by LC‐HRMS, as the main responsible for the CTX toxicity in the samples from the areas selected for this study. The low concentrations levels of CTXs found on the samples evaluated has been a key limitation for the completion of the objectives of this specific grant (SG), being necessary to establish contingency plans, not only to overcome the problems of sensitivity that might compromise the confirmation of the toxic profiles, but also to accomplish the task of preparing reference materials. The contingency plans involved the development of two complementary LC‐MS/MS approaches, as well as a methodological approach combiningLC‐MS/MS, Neuroblastoma cell assay and chromatographic fractionations (HPLC and GPC) to characterize the toxins present in the contaminated extracts. This approach has been also used for the preparation of reference materials in order to confirm the presence of the C‐CTX1 in both pure solutions of C‐CTX1 and Fish Tissue Reference materials (FTRM) containing C‐CTX1. The LC‐MS/MS analysis of Dinoflagellates samples ( Gambierdiscus and Fukuyoa sp) allowed to confirm the lack of correlation between the CTXs contamination and the fish samples from the areas were these dinoflagellates were collected. In these samples, the toxicity was attributed to several Maitotoxins analogues as well as gambieric acids C and D, Gambierone, 44‐methyl gambierone, and gambieroxide that were identified by LC‐HRMS with varying degrees of confirmation in strains of Gambierdiscus and Fukuyoa from the Mediterranean Sea and North East Atlantic Ocean.